Kompleks Polielektrolit Kitosan-Xanthan sebagai Matriks Sediaan Mukoadhesif - Setio Putri, Kurnia Sari; Sulistomo, Bambang; Surini, Silvia (UI Scholars Hub, 2017)
Mucoadhesive dosage form is a pharmaceutical dosage form with prolonged gastric residence time which can increase bioavailability of drugs. An excipient with suitable swelling and bioadhesive characteristics plays important role to obtain good mucoadhesive dosage form. Our pre-eliminary study showed that chitosan-xanthan gum polyelectrolyte complex (CXPC) in ratio 1:1 exhibit suitable swelling index to be developed as mucoadhesive dosage forms. This research was performed to study CXPC characteristics as matrix for mucoadhesive granules dosage form matrix. In this study CXPC 1:1 was utilized as the matrix in the mucoadhesive granules with drug-CXPC ratio of 1:1, 1:2, and 1:3, using diltiazem HCl as a drug model. The granules were prepared by wet granulation method, and the in vitro bioadhesive properties of the granules, as well as the drug release profile, were evaluated. The results showed that formula containing diltiazem HCl and CXPC in ratio of 1:2 possessed a good bioadhesive ability up to 8-12 hours and showed controlled drug release profile up to 8 hours. The results can be concluded that the CXPC is a suitable excipient as a mucoadhesive matrix.